Development Of Learning Multimedia In Mathematics Subjects For Grade III Elementary School Students - Rosman, Zaidinatul; Hidayati, Abna (Universitas Negeri Padang, 2023)
The background of this research is due to several facts found in the field. This is because students have difficulty understanding the concept of multiplication and division and students have difficulty understanding multiplication and division of two-digit numbers. This study aims to produce learning multimedia products in Mathematics class III SD that are valid, practical, and effective.This type of research is development research known as Research and Development (R&D), using the 4-D development model. The development procedure in this study consisted of 4 stages namely; (1) Define, (2) Design, (3) Develop, (4) Disseminate. The product validity test was carried out by 3 validators, namely 1 material expert validator and 2 media expert validators. Product trials were carried out on 20 third grade students at SD Negeri 27 Limau Asam with the aim of knowing the practicality and effectiveness of the product being developed. Development of learning multimedia, the results of which were assessed by 2 material and media validators, each of which was categorized as